SIMULATION MODELING OF MOTION ON PEDESTRIAN CROSSING, EQUIPPED WITH A TRAFFIC LIGHT - Дехтярук, Микола (SWorldJournal, 2022)
The article is devoted to modern computer information technologies. The system of simulation modeling GPSS World is considered, for the purpose of movement modeling on a pedestrian crossing equipped with traffic light adjustment. A simulation model of a p